2022
DOI: 10.31557/apjcp.2022.23.10.3571
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between CD44 and Angiogenesis in Oral Squamous Cell Carcinoma Induced in Buccal Pouch in Syrian Hamster that Underwent Radiotherapy

Abstract: Background: Angiogenesis with radiotherapy is a significant focus of recent studies to confirm the importance of combined treatments, as vascular control can have a great therapeutic target. Vascular endothelial growth factor is the key mediator of angiogenesis in cancer. In addition, some studies suggest the value of CD44 as a potential early marker of angiogenesis. Objectives: Investigating the expression of vascular endothelial growth factor (VEGF) and CD44 in oral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…In addition, tumour cells that were resistant to radiotherapy showed positive expression of VEGF. These findings suggest that VEGF expression may be associated with radioresistance in OSCC ( 74 ). In conclusion, VEGF has a significant role in the pathogenesis and progression of OSCC.…”
Section: Serological Markersmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, tumour cells that were resistant to radiotherapy showed positive expression of VEGF. These findings suggest that VEGF expression may be associated with radioresistance in OSCC ( 74 ). In conclusion, VEGF has a significant role in the pathogenesis and progression of OSCC.…”
Section: Serological Markersmentioning
confidence: 74%
“…Furthermore, Alsafadi and Manadili ( 74 ) investigated the expression of VEGF in OSCC after inducing it in hamsters and subjecting them to radiotherapy. The results showed that VEGF expression was not significantly different between the group that received radiotherapy and the group that did not.…”
Section: Serological Markersmentioning
confidence: 99%
“…The relationship between these two markers could also pave a path towards the possible mechanism dictating this radioresistance. Hence, combining VEGF or CD44 inhibitors with RT would be an acceptable option for achieving a better treatment outcome ( 157 ).…”
Section: Extrinsic Factors Governing Oscc Stemnessmentioning
confidence: 99%